Multi-Source Glacial Lake Outburst Flood Hazard Assessment and Mapping for Huaraz, Cordillera Blanca, Peru - Frey, Holger; Huggel, Christian; Chisolm, Rachel E.; Baer, Patrick; McArdell, Brian; Cochachin, Alejo; Portocarrero, César (Frontiers in Earth Science, 2018)
The Quillcay catchment in the Cordillera Blanca, Peru, contains several glacial lakes, including Lakes Palcacocha (with a volume of 17 x 106 m3), Tullparaju (12 x 106 m3) and Cuchillacocha (2 x 106 m3). In 1941 an outburst of Lake Palcacocha, in one of the deadliest historical glacial lake outburst floods (GLOF) worldwide, destroyed large parts of the city of Huaraz, located in the lowermost part of the catchment. Since this outburst, glaciers and glacial lakes in Quillcay catchment have undergone drastic changes, including a volume increase of Lake Palcacocha between around 1990 and 2010 by a factor of 34. In parallel, the population of Huaraz grew exponentially to more than 120,000 inhabitants nowadays, making a comprehensive assessment and mapping of GLOF hazards for the Quillcay catchment and the city of Huaraz indispensable. Here we present a scenario-based multi-source GLOF hazard mapping, applying a chain of interacting numerical models to simulate involved cascading mass movement processes. Susceptibility assessments for rock-ice avalanches and breach formation at moraine dams were used to define scenarios of different magnitudes and related probabilities, which are then simulated by corresponding mass movement models. The evaluation revealed, that (1) the three investigated lakes pose a significant GLOF hazard to the Quillcay Catchment and the city of Huaraz, (2) in some scenarios the highest hazard originates from the lake with the smallest volume (Cuchillacocha), and (3) current moraine characteristics of Lake Palcacocha cannot be compared to the situation prior and during the 1941 outburst. Results of outburst floods obtained by the RAMMS model were then converted into intensity maps and corresponding hazard levels according to national and international standards, and eventually combined into the GLOF hazard map for the entire Quillcay catchment, including the urban area of Huaraz. Besides technical aspects of such a multi-source model-based hazard mapping, special attention is also paid to approval and dissemination aspects in a complex institutional context. Finally, some general conclusions are drawn and recommendations are given, that go beyond the presented case of the Quillcay Catchment.